(untitled) - Bastin, John (New Jersey, 1970)
The history of the Southeast Asian peoples has been tightly intertwined with Western colonialism since the arrival of Portuguese traders in the early 1500's. Yet, as the authors of this book explain, "Western colonialism, though diverting much of Southeast Asian life from its peculiar, indigenous course, did not necessarily cancel out ago-old traditions and institutions." John Bastin and Harry J. Benda combine colonial history with social history to provide a sharply focused, twofold analysis of the Southeast Asian region. Stressing comparative interpretations, the authors describe the growth of the colonial regimes, the Southeast Asian response to the West, the crucial period of Japanese occupation, and the difficulties of modern decolonization.
Keywords: Đông Nam Á,Southeast Asia; Lịch sử,History